Marine Purple Photosynthetic Bacteria as Sustainable Microbial Production Hosts - Higuchi-Takeuchi, Mieko; Numata, Keiji (Frontiers in Bioengineering and Biotechnology, 2019)
Photosynthetic microorganisms can serve as ideal hosts for sustainable production of high-value compounds. Purple photosynthetic bacteria are typical anoxygenic photosynthetic microorganisms and are expected to be one of the suitable microorganisms for industrial production. Purple photosynthetic bacteria are reported to produce polyhydroxyalkanoate (PHA), extracellular nucleic acids and hydrogen gas. We characterized PHA production as a model compound in purple photosynthetic bacteria, especially focused on marine strains. PHA is a family of biopolyesters that a variety of microorganisms accumulate as carbon and energy storage materials and recently have attracted attention as alternative to conventional petroleum-based plastics. Production of extracellular nucleic acids have been studied in Rhodovulum sulfidophilum, a marine purple nonsulfur bacterium. Several types of artificial RNAs have successfully produced in R. sulfidophilum. Purple photosynthetic bacteria produce hydrogen via nitrogenase, and genetic engineering strategies have been investigated to enhance the hydrogen production. This minireview describes the microbial production of these high-value compounds using purple photosynthetic bacteria as host microorganism.